Досвід та перспективи розвитку міждисциплінарної освіти - Калашніков, Віктор Іванович; Левшов, Олександр Васильович; Ткаченко, Сергій Миколайович (НТУ "ХПІ", 2013)
The article considers the experiences and perspectives of interdisciplinary education. A detailed analysis of the curriculums masters training in electroenergetics. The paper suggested in the preparatory phase of masters in the period of theoretical training to provide specialized training in a wide range of interdisciplinary education, and to provide scientific topics related to the area of future employment.
Keywords: міждержавні енергетичні системи; об’єднання наукових зусиль; академічне партнерство; міждисциплінарна підготовка фахівців; підготовка бакалаврів; підготовка магістрів